The aspirin in reducing events in the elderly trial: Statistical analysis plan - Wolfe, R.; Murray, A.; Woods, R.; Kirpach, B.; Gilbertson, D.; Shah, R.; Nelson, M.; Reid, Christopher; Ernst, M.; Lockery, J.; Donnan, G.; Williamson, J.; et al. (Wiley-Blackwell Publishing Asia, 2018)
Rationale: Aspirin has positive and negative effects on a number of age-related chronic conditions and there is uncertainty regarding its role in primary prevention in people aged 70 years and over. Aims: To assess whether daily active treatment of 100 mg enteric-coated aspirin will extend the duration of disability-free life in healthy older participants. Design: A double-blind, randomized, placebo-controlled primary prevention trial undertaken in Australia and the United States with careful adjudication of endpoints including stroke. Study outcome: In Australia 16,703 individuals were recruited through general practices across five states and territories, and in the United States, 2411 participants were recruited through 34 clinical sites across the country. Follow-up of participants will finish at the end of 2017 with average follow-up exceeding 4.25 years per person. Discussion: The statistical analysis plan for ASPREE, finalized after closure of recruitment but before the end of patient follow-up, outlines the primary analyses and a range of subgroup and sensitivity analyses. (International Standard Randomized Controlled Trial Number Register ISRCTN83772183 and clinicaltrials.gov Number NCT01038583).